Laporan Kasus: Fibrosarkoma Vagina Pada Anjing Golden Retriever - Ahmad, Fauzi; Haryo, Albiruni; Permata, Fajar Shodiq; Titisari, Nurina (Jurnal Veteriner; Vol 22 No 1 (2021), 2021)
A Golden Retriever bitch, 10 years old, came to the Animal Hospital of Brawijaya University, Malang, Indonesia, her conditions was discharge from the vagina, stink smell, polyuria, polydipsia and swelling in the vaginal area that begin to appear one month ago.  Physical examination results found her weight 30 kg, scored three for body condition score (scale 1-5), body temperature at 38ºC, pale mucous membrane, and Capillart Reill Time > 2 seconds.  Hard mass was palpable in the vaginal area.  Based on the anamnesis, physical examination and clinical symptoms, the bitch appeared have some different diagnosis such as pyometra, endometritis, vaginitis, and vaginal tumors.  Hematology, radiograph, and histopathological laboratory tests were performed to confirm the diagnosis.  Hematologic results showed the bitch suffered from leukocytosis of 41.7 x 103/?L, granulocytosis 36.5 x 103/?L, and hyperchromic microcytic anemia.  The results of the radiograph examination showed a radiopaque solid mass in the vagina and uterus. The results of the histopathological examination found there were hyperchromasia nuclei and pleomorphism of fibroblast cell, and formation spindles cell of connective tissue. Based on the results of physical examination, hematological test, radiographic test, and histopathology, the dog was diagnosed with fibrosarcoma in the vagina. The treatment of this case was ovariohysterectomy and removal of the vaginal tumor. Early diagnosis and early treatment largely determine the patient’s prognosis, metastatic vaginal fibrosarcoma tumors showed poor prognosis.